Dust fall device for atmospheric environment governance - ZHANG XINGZI; JIA HAIFENG; LI SEN; LIU YUEXIONG (2022)
The utility model provides a dust fall device for atmospheric environment governance, which comprises a device shell, a mounting groove is arranged on the outer wall of the top of the device shell, a rotating mechanism is arranged on the inner wall of the bottom of the mounting groove, and a rotating plate is arranged on the top of the rotating mechanism. The circumference of the rotating plate is connected with the inner wall of the mounting groove through a bearing, the top of the rotating plate is fixedly connected with a water pump, the water pumping end of the water pump is fixedly connected with a water tank through a water drainage pipe, the water tank is fixedly connected with the rotating plate, and the water drainage end of the water tank is fixedly connected with a water conveying pipe. A plurality of evenly-distributed atomizing nozzles are fixedly connected to a water outlet of the water conveying pipe through connecting valves, dust removal mechanisms are arranged on the outer wall of the periph